Հաղբատի գրչության կենտրոնը - Թերզյան, Գայանե («Նաիրի» հրատ.)
The Monastery of Haghbat was founded in 976 by Khosrovanush, the wife of Ashot III the Merciful. Soon a scriptorium was created here. Scribe Simeon was the first prior and he himself copied the first manuscript in 999, namely, St. Paul’s Epistles and Commentary on them by John Chrysostom and Ephrem the Syrian; it is considered the second oldest Armenian manuscript on paper. The 13th and 15th centuries were very productive for the Haghbat scriptorium. The History of Armenia by Aristakēs Lastivertsʻi copied by Yovhannēs Erznkeantsʻ in 1840 is the last manuscript copied in the scriptorium. Монастырь Ахбат был основан в 976 году усилиями царицы Хосровануш, жены царя Ашота III Милосердного. Вскоре здесь был создан скрипторий. Писец Симеон стал первым настоятелем Ахбатского монастыря, а в 999 году он завершил свою первую рукопись: “Послание апостола Павла, с толкованиеми Ефрема (Сирина) и Иоанна Златоуста”, которая считается второй самой древней рукописью на бумаге. XIII-XV века считаются самыми плодовитыми в истории Ахбатского монастыря. В 1840 году писец Оганес Ерзнкянц скопировал Историю Армении Аристакеса Ластиверци, последнюю работу скриптория.
Keywords: Ձեռագրական ժառանգություն; Գրչություն